Penerapan Model Permainan Untuk Meningkatkan Hasil Lompat Jauh Pada Siswa Kelas V Sekolah Dasar - Muhazir, Ahmad; Gusril, Gusril; Neldi, Hendri (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This study aimed to improve long jump learning outcomes of fifth-grade students at SD Islam Khairu Ummah Padang through the implementation of a game-based learning model. The research employed Classroom Action Research conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 36 students. Data were collected through observation and long jump performance tests and analyzed using descriptive, quantitative, and qualitative techniques. The results indicated that the game-based learning model significantly improved students’ learning outcomes. In Cycle I, the average score was 48.92 with a mastery level of 22.22%. After improvements in Cycle II, the average score increased to 83.06, with learning mastery reaching 94.44%. These findings demonstrate that the game-based learning model is effective in enhancing long jump skills among elementary school students.